2007
DOI: 10.1177/0165025406073530
|View full text |Cite
|
Sign up to set email alerts
|

White lie-telling in children for politeness purposes

Abstract: Prosocial lie-telling behavior in children between 3 and 11 years of age was examined using an undesirable gift paradigm. In the first condition, children received an undesirable gift and were questioned by the gift-giver about whether they liked the gift. In the second condition, children were also given an undesirable gift but received parental encouragement to tell a white lie prior to being questioned by the gift-giver. In the third condition, the child's parent received an undesirable gift and the child w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
194
3
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(214 citation statements)
references
References 36 publications
13
194
3
4
Order By: Relevance
“…They do this more when the gift giver is present than absent, suggesting that they do it to maintain a positive relationship with the gift giver. In a related study, Talwar, Murphy, and Lee (2007) found that, with increasing age, children were more likely to tell a white lie to disguise their disappointment with an inadequate gift and that they were more likely to smile as they told this white lie as well. Children"s ability to use social acting to maintain positivity in social relationships  something which is also beginning to develop during this same age range and which likely also evolved for the maintenance of…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…They do this more when the gift giver is present than absent, suggesting that they do it to maintain a positive relationship with the gift giver. In a related study, Talwar, Murphy, and Lee (2007) found that, with increasing age, children were more likely to tell a white lie to disguise their disappointment with an inadequate gift and that they were more likely to smile as they told this white lie as well. Children"s ability to use social acting to maintain positivity in social relationships  something which is also beginning to develop during this same age range and which likely also evolved for the maintenance of…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Evidence that they do so comes from research on white lies (that is, lies told in order to spare the feelings of a social partner). Talwar et al [78] investigated how 3-to 11-year-old children responded when they received a disappointing gift from an experimenter. Although children showed their disappointment when alone, when the experimenter returned and asked them whether they liked the gift many answered that they did, and this was true even in the youngest children (see also [79,80]).…”
Section: (B) Forming and Maintaining Long-term Bondsmentioning
confidence: 99%
“…Children's ability to maintain their lies and avoid detection has been shown to increase with age [20,[22][23][24][25]. Specifically, young children often have difficulty maintaining consistency throughout false statements and as a result incriminate themselves by leaking critical information about their own deceit [20,21,24]. As children grow older (especially after the age of 6 years), their ability to elaborate on lies and to maintain consistency across false statements increases [25].…”
Section: Journal Of Criminologymentioning
confidence: 99%